O Niewygodzie - Pietrych, Krystyna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The text provides a detailed interpretation of the poem Niewygoda (Discomfort), written by Iwaszkiewicz at the end of his life, situated among other achievements of his late poetry and confronted with his diary entries. The main issues addressed here concern the meanings that arise at the level of versification, lexis, style and composition of the analyzed work. The poet uses tropes that constitute a departure from his earlier typical poetics characterized by discretion and moderation. This poem becomes a poignant, deeply personal confession filled with a dramatic sense of somatic pain of old age and the intuition of approaching death.